Heromice : Charge of the Clones - Stilton, Geronimo (United States, India Scholastic, 2017)
Heromice #8: Charge of the Clones is a children's adventure book by Geronimo Stilton where the Heromice$1 (BGeronimo, Thea, and Trap$1 (Bmust defend Muskrat City from a bizarre crime wave. s
English
Keywords: Children's Literature; Action & Adventure; Science Fiction/Fantasy